Development of a Novel Analytical Method for Determining Trazodone in Human Plasma by Liquid Chromatography Coupled With Mass Spectrometry Coupled With Automatic 2-Dimensional Liquid Chromatograph-Mass Spectrometer Coupler 9500 and Its Application to Therapeutic Drug Monitoring. Issue 3 (June 2022) - Ding, Jing; Zhang, Yan; Cui, Xiaohua; Zhao, Caiping; Zhang, Suo
Abstract : Background: Trazodone (TZD) is a tetracyclic serotonin antagonist and reuptake inhibitor that is used as a second-generation phenylpiperazine antidepressant. However, the plasma concentrations of TZD have shown individual variations in clinical practice. Quantification of TZD plasma concentrations may be an effective and valuable method to balance the clinical efficacy and adverse reactions. This study aimed to establish a novel liquid chromatography coupled with mass spectrometry (LC-MS) assay for measuring TZD concentrations in human plasma for therapeutic drug monitoring (TDM). Methods: After protein precipitation with acetonitrile, LC-MS quantification of TZD was performed in the multiple reaction monitoring mode with chromatographic separation using a mobile phase of MeOH and 0.1% formic acid in water. This method validation intends to investigate specificity, sensitivity, linearity, precision, accuracy, recovery, matrix effect, and stability according to United states food and drug administration guidelines. Results: This method showed good selectivity because no interfering peaks were observed in the plasma samples during the 2-minute run time. The range of the calibration curve was 1–3000 ng/mL. The detection and quantification limits were 0.3 and 1 ng/mL, respectively. The intraday and interday accuracies were 96.5%–103.4%, with precision relative SD% values of <5%, except for the limit of quality. The mean TZD recovery from human plasma was 95.4%–104.5%. Finally, this method was successfully applied to TDM in 20 patients. The TZD plasma concentrations of the patients ranged between 21.5 and 2267.3 ng/mL. Conclusions: A novel analytical method was established to measure TZD by LC-MS coupled with an automatic 2-dimensional liquid chromatograph mass spectrometer coupler 9500 (LC-MS/MS-Mate 9500), which is superior to the ordinary LC-MS system in separation, transport, anti-interference, sensitivity, and quantitative analysis stability.